Analysis Of District Court Decision On Human Trafficking In Constitutional Court Decision Number 32/PUU-XV/2017 - Abdul Mukhsin Abdat; Jfrans Ananda Pratama Tarigan S; Muhammad Qodafi Lubis; Bima Sakti; Muhammad Khairul Fahmi; Muhammad Fariz; Abdul Halim Nasution (SEAN Institute, 2025)
This study aims to analyze the implementation of the Law on the Crime of Human Trafficking (UU TPPO) in Indonesia with a focus on the role of court decisions, prevention efforts, and victim protection in eradicating human trafficking practices. The methods used in this study are qualitative and descriptive approaches. The results of the study indicate that although court decisions have attempted to apply sanctions in accordance with the TPPO Law, victim protection is still not optimal, especially in terms of psychological and economic rehabilitation which are often unsustainable. Uneven prevention campaigns in vulnerable areas such as rural areas and borders are also a challenge in breaking the chain of human trafficking. Therefore, it is necessary to strengthen the capacity of law enforcement officers, increase cooperation with civil society organizations, and conduct wider socialization so that the public can better understand the impacts and risks of TPPO. This study emphasizes the importance of a holistic approach involving strict law enforcement, maximum victim protection, and community-based prevention to effectively eradicate TPPO.